2009
DOI: 10.1108/00021460910978652
|View full text |Cite
|
Sign up to set email alerts
|

The impact of board of director characteristics on Farm Credit Association performance

Abstract: Purpose -The purpose of this paper is to identify how board size and board member compensation impact the operating performance of Farm Credit Associations. Cooperatives are a unique business structure that might not have profit maximization as a goal. Thus measures of performance other than return on equity are used to establish the link. Design/methodology/approach -The paper uses regression to explain the relationship between board characteristics and performance. Findings -The results of the models of retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…The various groups of people on the board become a value-maximizing board, which is likely to resolve the intimidations as it can reduce the riskiness of investments, as well as effectively maintain the channel of communication with the diverse group of stakeholders (Faleye and Krishnan, 2017). A similar line of study by Gunderson et al . (2009) also point out the effectiveness of board while they argued that a board consisting of an increasing number of decision-makers with diversified characteristics, can easily handle the impediment and improve the corporate performance, minimize the risks and inject the agricultural credit issues in the decision-making process for strategizing the grating of agro-capital.…”
Section: Introductionsupporting
confidence: 82%
“…The various groups of people on the board become a value-maximizing board, which is likely to resolve the intimidations as it can reduce the riskiness of investments, as well as effectively maintain the channel of communication with the diverse group of stakeholders (Faleye and Krishnan, 2017). A similar line of study by Gunderson et al . (2009) also point out the effectiveness of board while they argued that a board consisting of an increasing number of decision-makers with diversified characteristics, can easily handle the impediment and improve the corporate performance, minimize the risks and inject the agricultural credit issues in the decision-making process for strategizing the grating of agro-capital.…”
Section: Introductionsupporting
confidence: 82%
“…Financial performance ratios and organizational survival has also been discussed at great length in the agricultural finance literature. For instance, Gunderson, Gloy and Rodgers (2009) show that board size and director compensation of U.S. Farm Credit Associations explain little of the variability in performance ratios such as return on equity (ROE) and return on assets (ROA).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found a negative relationship between board size and asset utilization (Reddy & Locke, 2014), ROA (Franken & Cook, 2019; Reddy & Locke, 2014), ROE (Franken & Cook, 2019), overall performance (Franken & Cook, 2019), operating efficiency (Gunderson et al, 2009), operating expenses to earning assets ratio (Gunderson et al, 2009), and cost-efficiency (Yamori et al, 2017). Some studies suggest that board size may not be linked with ROA and ROE (Gunderson et al, 2009); profit efficiency (Yamori et al, 2017); net interest income, return on loans, cost of funds, and total operating cost (Ghosh & Ansari, 2018); extra-value index (Franken & Cook, 2019); and net premium written, expense ratio, and profit margin (Hemrit, 2020). However, Hakelius (2018) reports that board size has a positive effect on cooperative performance.…”
Section: Content Analysismentioning
confidence: 99%
“…This result underscores the importance of the cooperative concept appreciation to the core and the appointment of a competent cooperative member as the CEO of a cooperative. The relationship between cooperative board characteristics and performance has been investigated mainly in cooperatives in the fields of agriculture (e.g., Gunderson et al, 2009;J. Rebelo et al, 2011) and financial/insurance (e.g., Ghosh, 2018;Yamori et al, 2017).…”
Section: Boardmentioning
confidence: 99%